Ammophila nancy Menke, a new species in the pruinosa complex (Hymenoptera: Sphecidae: Ammophilinae) - Menke, Arnold S. (Zootaxa, 2007)
Ammophila nancy new species (Hymenoptera, Sphecidae), is described from Arizona, California, Nevada, New Mexico, Texas and Mexico (Sonora and Baja California). The new species is a member of the pruinosa complex which also contains californica Menke, 1964, and pruinosa Cresson, 1865. A key is provided for the identification of the three species.